2016
DOI: 10.1007/s00705-016-2904-x
|View full text |Cite
|
Sign up to set email alerts
|

Activation of toll-like receptor signaling pathways leading to nitric oxide-mediated antiviral responses

Abstract: Toll-like receptors (TLRs), well-characterized pattern-recognizing receptors of the innate arm of the immune system, are vital in detecting pathogen-associated molecular patterns (PAMPs). The TLR-PAMP interaction initiates an intracellular signaling cascade, predominantly culminating in upregulation of antiviral components, including inducible nitric oxide synthase (iNOS). After activation, various TLR pathways can promote iNOS production via the myeloid differentiation primary response-88 (MyD-88) adapter pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
52
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(58 citation statements)
references
References 153 publications
(147 reference statements)
3
52
0
3
Order By: Relevance
“…Ultimately, we found that after 24 h of renal I/R, the expression levels of HMGB1, MyD88, TRIF, NF-κB p65, ERK, and p38 mRNA and protein in the WT mice were higher than those in the TLR4 -/-mice and were higher in the HMGB1 group than in the I/R group. TLR, a well-featured pattern-recognizing receptor of the innate immune system, is crucial in initiating an intracellular signaling cascade; after activation, various TLR pathways can promote the expression of factors, such as MyD-88 adapter protein [41], as well as IFN-β, IKK-α and IKK-β genes [42]. Additionally, the results showed that the expression levels of TLR signaling pathway-related genes were elevated in the HMGB1 group compared with those in the I/R group, suggesting that the injection of HMGB1 can activate the TLR signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Ultimately, we found that after 24 h of renal I/R, the expression levels of HMGB1, MyD88, TRIF, NF-κB p65, ERK, and p38 mRNA and protein in the WT mice were higher than those in the TLR4 -/-mice and were higher in the HMGB1 group than in the I/R group. TLR, a well-featured pattern-recognizing receptor of the innate immune system, is crucial in initiating an intracellular signaling cascade; after activation, various TLR pathways can promote the expression of factors, such as MyD-88 adapter protein [41], as well as IFN-β, IKK-α and IKK-β genes [42]. Additionally, the results showed that the expression levels of TLR signaling pathway-related genes were elevated in the HMGB1 group compared with those in the I/R group, suggesting that the injection of HMGB1 can activate the TLR signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…24,25 The presence of TLR2 and TLR4 has been shown to be essential for the progression of inflammation and related bone metabolism in periodontitis. 16,26 However, little is known about the specific contributions of TLR2 and TLR4 signaling in different models of experimental periodontitis in mice.…”
Section: Discussionmentioning
confidence: 99%
“…Since TLR activation has been shown to promote the expression of nitric oxide synthase (NOS) (Xiong et al 2004)Abdul-Cader et al 2016) and nitric oxide species are modulators of DC physiology (Verinaud et al 2015), we evaluated the role of this pathway in the maturation of DCs upon activation of TLR9 and TLR7. Thus, we incubated DC preparations with TLR agonists in the presence of a NOS inhibitor, L-NAME (Adler et al 2010), and assessed the secretion of IL-12 and IL-10, as well as the ability of DCs to support allogeneic splenocyte proliferation (Fig.…”
Section: Role Of Nos and Ido In Tlr-mediated Activation Of Dcsmentioning
confidence: 99%
“…Although the effect of IDO on the suppression of T lymphocyte proliferation and function has been extensively described, the role of this enzyme on the maturation of DCs is not fully understood. On the other hand, TLR activation can also promote the expression of nitric oxide synthase (NOS) via MyD88 adapter protein and NF-κB activation (Abdul-Cader et al 2016;Xiong et al 2004). However, the role of NOS on the maturation of DCs also remains controversial and it has been proposed as a positive (Paolucci et al 2003;Verinaud et al 2015) or a negative (Obregon et al 2015) mediator of DC maturation.…”
Section: Introductionmentioning
confidence: 99%